UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA NILAI-NILAI AGAMA ISLAM DI SMK NEGERI 05 BENGKULU SELATAN - Emy Herawati (Universitas Islam Negeri Fatmawati Sukarno, 2021)
Abstract. Background in research is islamic values consisting of 3 points that cannot be separated because they depend on each other, namely: The Value of Creed, Sharia Values, and Moral Values. So with this formation will be formed individuals who are Muslims who are noble, obedient to Allah and his apostles, respectful to the mother and love to his fellow mahlik creation of Allah. And PAI teachers are an example for students in the development of these religious value. The formulation of the problem in this study is what are the efforts of Islamic Religious Education teachers in fostering the values of The Creed in SmK Negeri 05 Bengkulu Selatan, what are the efforts of Islamic Religious Education teachers in fostering sharia values in SMK Negeri 05 Bengkulu Selatan, and what are the efforts of Islamic religious education teachers in fostering moral values in SMK Negeri 05 Bengkulu Selatan. The purpose od the research is to analyze what efforts PAI teachers make in fostering sharia values, and to analyze what efforts PAI teachers make in fostering moral values in SmK Negeri o5 Bengkulu Selatan. The data source used is sourced from pai smk negeri 05 teachers, and students of SMK Negeri 05 Bengkulu Selatan.Research data collection tools are observation, interview, documentation. The results of this study are (1) the efforts of PAI teachers in fostering the values of the creed, among others, spiritual flushing every Friday, bedoa before and after learning, reading quranic verses and lqra every meeting at the beginning of Islamic religious learning, extracurricular rohis. (2) Pai teachers' efforts in fostering sharia values include the habituation of dzuhur prayer, requiring that women wear hijab. (3) PAI teachers' efforts in building moral values include the habituation of greetings, habituation of giving good advice, and environmentally friendly refraction.Keywords: Teacher of Islamic Religious Education, Islamic Religious Values